Enabling and Predisposing Factors for the Utilization of Preventive Dental Health Care in Migrants and Non-Migrants in Germany - Brzoska, Patrick; Erdsiek, Fabian; Waury, Dorothee (Frontiers in Public Health, 2017)
Background: In many European countries including Germany migrants utilize preventive services less frequently than the majority population. This is also true for the utilization of dental check-ups. Little is known about which demographic, social, behavioral and health-related factors influence the decision of migrants to seek preventive dental health care and how these factors differ from those in non-migrants. The aim of the present study was to examine the role of these factors among migrants and non-migrants residing in Germany. Methods: Data from cross-sectional national health surveys is used, providing information on preventive dental health behavior from n=41,220 individuals, of which 15.0% are migrants. Anderson’s Behavioral Model of Health Services Use is the conceptual framework of the investigation. Multiple logistic regression models were applied to examine the role of different predisposing and enabling factors. Interaction terms were included in order to examine whether determinants differ between migrants and non-migrants. Average marginal effects (AME) are reported in addition to odds ratios (OR) as measures of effect size which are robust against bias arising from unobserved heterogeneity. Results: Migrants are at an about 36% lower chance of utilizing regular dental check-ups than non-migrants (OR=0.64[95%-CI=0.61,0.68];AME=-0.081[95%-CI=-0.093,-0.069]). Differences are partly explained by the influence of demographic, social, behavioral and health-related factors (adjusted OR=0.69[95%-CI=0.64,0.73];AME=-0.065[95%-CI=-0.076,-0.053]). Younger age, being male, lower socioeconomic status, a non-statutory health insurance, not living in a relationship, living in the Western part of Germany and in an urban setting and poor limited social support were associated with a lower chance of utilizing regular dental check-ups. Interaction effects could be observed for age and type of health insurance. Discussion: The study identifies different enabling and predisposing factors that are relevant for the utilization of dental check-ups among the population in Germany, some of which differ between migrants and non-migrants. Differences are particularly pronounced for younger ages. This differs from findings on other preventive services where older migrants tend to be more disadvantaged. Additional explanatory factors such as barriers migrants experience in the dental health care system need to be considered in order to implement patient-oriented services and to reduce disparities in access to dental prevention.